Konsultasi TPA dengan Pemohon PBG Pendirian Pabrik Pengolahan Kelapa Sawit Kapasitas 5 Ton/Jam PT. XX - Purwo Subekti; Bambang Edison; Anton Ariyanto; Taufik Kurniawan (CV. Multi Kreasi Media, 2025)
Community Service through Consultation by the Professional Team of Experts (TPA) regarding the technical and administrative requirements that must be fulfilled to obtain Building Approval (PBG) involves consultation and examination of technical documents by TPA together with the applicant. The purpose of this activity is to ensure the completeness and compliance of PBG application documents, especially in the project of establishing a Mini Palm Oil Processing Plant with a Capacity of 5 Tons/Hour by PT. XX. The results of the first consultation indicate that there are several documents that still need to be revised and provided with additional explanations, such as detailed lightning rod drawings, plumbing details, and illustrations of wastewater treatment ponds. Recommendations provided by TPA must be carefully considered and effectively implemented to ensure that the technical documents meet the applicable standards.The second consultation shows that most of the recommendations from the previous consultations have been implemented. However, there are still some technical aspects that require further explanations and improvements. After all recommendations have been fulfilled, TPA and the applicant agreed to proceed with the PBG application process to the relevant authorities. The consultation and document examination process conducted is expected to provide clear guidance for the applicant and ensure that the project for establishing the Mini Palm Oil Processing Plant with a capacity of 5 Tons/Hour by PT. XX proceeds in accordance with the applicable technical standards and regulations. A strong synergy between TPA, the applicant, and the relevant authorities is expected to create smoothness and success in the licensing and project development process.